2014
DOI: 10.1371/journal.pone.0112900
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming Suppresses Premature Senescence Phenotypes of Werner Syndrome Cells and Maintains Chromosomal Stability over Long-Term Culture

Abstract: Werner syndrome (WS) is a premature aging disorder characterized by chromosomal instability and cancer predisposition. Mutations in WRN are responsible for the disease and cause telomere dysfunction, resulting in accelerated aging. Recent studies have revealed that cells from WS patients can be successfully reprogrammed into induced pluripotent stem cells (iPSCs). In the present study, we describe the effects of long-term culture on WS iPSCs, which acquired and maintained infinite proliferative potential for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 41 publications
5
63
2
Order By: Relevance
“…WRN plays a key role in chromatin homeostasis such as replication fork progression, base excision repair, and telomere maintenance 10) . Previous studies reported that dermal fibroblasts derived from WS patients could be reprogrammed into iPSCs 27) . Cells from patients with genetic disorders are an ideal tool for research; however, their application is limited in basic research, because it is difficult to obtain sufficient amounts of patientsʼ cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…WRN plays a key role in chromatin homeostasis such as replication fork progression, base excision repair, and telomere maintenance 10) . Previous studies reported that dermal fibroblasts derived from WS patients could be reprogrammed into iPSCs 27) . Cells from patients with genetic disorders are an ideal tool for research; however, their application is limited in basic research, because it is difficult to obtain sufficient amounts of patientsʼ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Because several reprogramming steps involve cell stress and extensive cell division, iPSCs may acquire chromosomal abnormalities during reprogramming. Previous reports showed that WS fibroblasts could be reprogrammed into iPSCs; however, the parental cultured fibroblasts already showed mosaicism with chromosomal abnormality 27) . We karyotyped the T lymphocyte-derived WS-iPSC lines, and observed that all the types of cells had normal karyotypes (Figure-2).…”
Section: Ws-ipscs Retained Normal Karyotypesmentioning
confidence: 96%
See 2 more Smart Citations
“…For instance, ectopic expression of telomerase results in lifespan extension of WS fibroblasts (Wyllie et al 2000). Reprogramming WS cells to specific lineages that naturally express telomerase also result in lifespan extension as was demonstrated in induced pluripotent and neuronal progenitor cells (Shimamoto et al 2014;Cheung et al 2014). …”
Section: Introductionmentioning
confidence: 91%